THE ROLE OF THE ALL-INDONESIAN TRADE UNION (SPSI) IN REALIZED WORKERS' WELFARE IN PADANG HILIR DISTRICT, TEBING TINGGI CITY - Rizki Aulia; Simson Ginting (OPINI: Journal of Communication and Social Science, 2025)
This study examines the role of the All-Indonesia Workers’ Union (SPSI) in promoting workers’ welfare in Padang Hilir District, Tebing Tinggi City. Using a descriptive qualitative approach, the research explores how SPSI provides legal protection, advocates workers’ rights, and strengthens workers’ bargaining power in negotiations with employers. Informants were selected through purposive sampling and included SPSI leaders, the Chairperson of the Plant-Level Union (PUK), and local workers. Data were collected through interviews, observation, documentation, and literature review. The findings indicate that SPSI Tebing Tinggi City has effectively fulfilled its role in protecting and defending workers’ rights. The union guarantees freedom of association, safeguards workers’ rights to fair wages, and encourages the creation of healthy and safe working environments. SPSI also actively negotiates with companies to improve wages, workers’ welfare, and employment agreements that prioritize workers’ interests. Additionally, SPSI serves as a channel for workers’ aspirations and complaints. However, the study finds that SPSI has not yet been able to provide systematic training or skills development programs for its members.